PELATIHAN PEMBUATAN WEBSITE DESA SEBAGAI PUSAT INFORMASI PROFIL DAN POTENSI DESA DI DESA WISATA PINGE KABUPATEN TABANAN - Widiartha, I.M.; Muliantara, A.; Astawa, I.G.S.; Harini, L.P.I.; Darmawan, I.D.M.B.A.; Ayuningsasi, A.A.K. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
Pinge Tourism Village is an old village that become one of the tourist destination in Bali. This village has its own uniqueness such as traditional architecture of house form and a neat parallel housing. Besides traditional architecture, Pinge Village has also a very beautiful natural scenery with a carpet of green rice fields stretching. Pinge was declared by the government as a tourism village in Bali Province. Tourism development requires a means of communication and promotion that allows all the people interact to promote the potential of Pinge village without being limited by space and time. The development of information and communication technology (ICT) has spawned website as a media to inform everyone through the internet. As an effort to develop Website of Pinge village, this community service is focused on training activities to village officers in developing and organizing a website. Output of this activity is a Pinge website application where all of the officers have been able to independently organize and manage the website of Pinge village.